EVALUASI PENERAPAN TARIF PPh PASAL 17 AYAT 2 UU NO. 36 TAHUN 2008 PADA PT SCK - Deta Krisnandy, P. Helen Widjaja, (Jurnal Ekonomi, 2016)
This case study was conducted to know the ratio of corporate income tax using the rates of Income Tax article 17, paragraph 2 and the rates of Income Tax article 4, paragraph 2 of Law Number 36 of 2008 on Income Tax and the impact acquired by corporate from the application of both of these rates. The results of this case study showed that the calculation of corporate income tax using Income Tax Article 17, paragraph 2 of Law Number 36 of 2008 had a positive impact for the corporate.